Moving the Existing City Towards Sustainability: The Role of Urban Planning - D’Onofrio, Rosalba (AESOP, 2012)
Transforming existing cities to align with sustainability principles is a challenging task. Nevertheless, European policies on urban regeneration highlight the urgency of pioneering strategies to address unsustainable urban models. This paper argues that while improvements may move cities toward greater sustainability, they will not necessarily result in fully sustainable cities. Urban planning’s role is to translate the pressures for adaptation into strategies, rules, and projects that integrate multiple disciplinary perspectives. Traditionally, urban planning has simplified urban systems, treating them as stable and predictable, while relegating responses to climate change to other disciplines, producing limited results. Today, there is growing recognition that promoting adaptation, resilience, and reversibility requires urban planning’s direct involvement. Recent international experiences with “Climate Plans” demonstrate this integration, linking climate action measures with urban planning. The paper examines how strategies to combat climate change can be incorporated into local government planning instruments, what new analytical tools are required, and how planning reasoning operates across different spatial scales. These strategies can support an evolving, dynamic urban planning process that remains open to continuous evaluation, verification, and stakeholder validation.
Book of proceedings : AESOP 26th Annual Congress 11-15 July 2012 METU, Ankara
Keywords: Sustainability; urban planning; climate change; resilience; adaptation; regeneration